The Role of the Constitutional Court in Upholding Constitutionality: A Case Analysis of the Constitutional Court's Decision on the Age Limit for Presidential and Vice Presidential Candidates in 2023: Peran Mahkamah Konstitusi Dalam Menjaga Konstitusionalitas: Analisis Kasus Putusan MK Tentang Batas Usia Capres Dan Cawapres Tahun 2023 - Putra, Firli Novansyah; Tambunan, Yunus; Ahmad, Hendry Andi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The Constitutional Court functions as a guardian of constitutional supremacy through judicial review within the Indonesian legal system. Specific Background: Decision Number 90/PUU-XXI/2023 concerning the presidential and vice-presidential age requirement introduced an alternative norm allowing candidates with prior elected experience despite not meeting the minimum age. Knowledge Gap: Previous studies have not simultaneously integrated constitutional interpretation, judicial ethics, and political implications arising from this decision. Aims: This study examines the constitutional reasoning, application of open legal policy, and ethical dimensions associated with the decision. Results: The analysis reveals that although the Court holds authority to interpret laws, the ruling generated controversy due to blurred boundaries between legislative and judicial domains, inconsistency in applying open legal policy, and indications of conflict of interest. Ethical violations involving constitutional judges further weakened institutional credibility and triggered public distrust. Novelty: This study integrates juridical analysis with constitutional political perspectives to assess both legal validity and democratic implications of the ruling. Implications: Strengthening judicial independence, reinforcing ethical compliance, and maintaining jurisprudential consistency are essential to preserve legitimacy and ensure stability within the constitutional system. Highlights• Judicial interpretation expands eligibility criteria beyond statutory age threshold• Ethical violations undermine institutional credibility and public trust• Legislative and judicial boundary ambiguity generates constitutional tension KeywordsConstitutional Court; Judicial Review; Legal Policy; Judicial Ethics; Constitutionality